Fatores de patogenicidade, perfil de resistência a antimicrobianos e diversidade clonal de Staphylococcus aureus isolados de leite cru, soro fermento, manipuladores e queijo Minas artesanal da região de Campo das Vertentes, Brasil - Renata Dias de Castro (2019)
Staphylococcus aureus is one of the main pathogens found in cheeses produced with raw milk, including Minas artisanal cheese from Brazil. However, information on S. aureus isolated from artisanal cheeses and its sources of production in small-scale dairies is very limited. We aimed to characterize the virulence aspects and clonal diversity of S. aureus isolated from Minas artisanal cheese, raw milk, endogenous starter culture and handlers from the region of Campo das Vertentes, Minas Gerais State, Brazil. The samples were identified by MALDI-TOF MS. Biofilm production was evaluated on Congo Red Agar (CRA) and polystyrene plates. PCR was used to detect icaA, icaB, icaC, sea, seb, sec, sed, see, tsst-1, agr and mecA. Expression of staphylococcal toxin genes in PCR positive samples was evaluated by qRT-PCR and the production of these toxins as well as hemolytic activity were in vitro evaluated. We also evaluated the antimicrobial resistance profile of the samples. For statistical analysis, cluster, chi-square test and correspondence were used. The study of the clonal diversity of the samples was performed by the spa typing, rep-PCR ((GTG)5) and MALDI-TOF MS techniques. The discriminatory power, the typability and the concordance between the typing techniques were evaluated. A total of 76 Staphylococcus aureus samples were analyzed. In the PCR, 18.42%, 18.42%, 2.63% and 77.63% of the samples were positive for sea, tsst-1, sec and agr, respectively. Staphylococcal toxin genes were of low expression in qRT-PCR and only two samples were TSST-producing. Most of the samples (61.84%) had hemolytic activity and were biofilm forming in CRA (69.73%) and in polystyrene plates (81.58%). None of the samples presented mecA neither presented a multiresistance pattern, with the highest resistance observed for Penicillin G (67.11%) and Tetracycline (27.63%). The most frequent genotype in the study was t605 (27%), followed by t002 (10.8%) and t521 (9.5%). Spa typing and (GTG)5 presented high discriminatory power, in contrast to MALDI-TOF MS, which presented low discriminatory power and low concordance with typification genomic techniques. In conclusion, the samples presented toxigenic potential, with a higher prevalence of sea and tsst-1. We found that the biofilm production was the main virulence factor of the samples. Six clusters were formed whose distribution frequencies differed 13 for hemolytic activity, biofilm formation (qualitative and quantitative analyses) and resistance to Penicillin, Tetracillin and Erythromycin (P <0.05). Staphylococcus aureus samples showed high genetic diversity, and there are evidences that the presence of this microorganism in the final product is the result of cross-contamination of raw milk, serum-yeast (pingo) and asymptomatic manipulators of this bacterial agent. These findings emphasize the need for effective measures to prevent staphylococcal food poisoning by limiting S. aureus growth and enterotoxin formation, , as well as reinforcing the importance of implementing good manufacturing practices to reduce the risk of transmission of potentially pathogenic bacteria along the cheesemaking chain.